Hero Elementary. Sparks' crew pet rescue! [videorecording (DVD)] - Hunt, Paul; Culbert, Marianne; Ferraro, Christine (Hero Elementary., 2021)
It's Sparks' crew to the rescue in ten pet-packed adventures! When an egg hatches and an unfamiliar bird emerges. Sparks' crew vows to reunite the bird with its parents. Then, a little girl's kitten is on the loose! Can the team observe how animals use their tails and apply that information to a rescue that will save the day?